1985
DOI: 10.1161/01.str.16.1.101
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic brain edema following occlusion of the middle cerebral artery in the rat. I: The time courses of the brain water, sodium and potassium contents and blood-brain barrier permeability to 125I-albumin.

Abstract: The present study was undertaken to analyze the roles of brain cations and of the blood-brain barrier (BBB) to albumin in the development of ischemic brain edema. Using the rat middle cerebral artery (MCA) occlusion model, changes in the brain water, sodium, and potassium contents were followed for a period of seven days. The permeability of the BBB to proteins was also followed by 125I-albumin transfer from the blood into the brain. A significant edema developed as early as three hours after MCA occlusion. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
126
0
4

Year Published

1987
1987
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 284 publications
(142 citation statements)
references
References 48 publications
12
126
0
4
Order By: Relevance
“…Although PMA slightly blunted the potassium loss associated with brain edema, this effect failed to reach statistical significance. These findings are consistent with the generally-accepted opinion that water and sodium tend to coexist, and move together through the plasma membrane under physiological and pathological conditions (Gotoh et al, 1985;Loo et al, 1996;Wright and Loo, 2000). Alternatively, in addition to the blunting of AQP4 upregulation by PMA, brain sodium channels may have been independently affected (Hourez et al, 2005).…”
Section: Discussionsupporting
confidence: 89%
“…Although PMA slightly blunted the potassium loss associated with brain edema, this effect failed to reach statistical significance. These findings are consistent with the generally-accepted opinion that water and sodium tend to coexist, and move together through the plasma membrane under physiological and pathological conditions (Gotoh et al, 1985;Loo et al, 1996;Wright and Loo, 2000). Alternatively, in addition to the blunting of AQP4 upregulation by PMA, brain sodium channels may have been independently affected (Hourez et al, 2005).…”
Section: Discussionsupporting
confidence: 89%
“…Brain edema that forms during the early hours of ischemic stroke involves a net uptake of Na + and water from blood into brain across an intact blood-brain barrier (BBB) (Betz, 1996;Betz et al, 1994Betz et al, , 1995Menzies et al, 1990Menzies et al, , 1993Schielke et al, 1991) along with swelling of astrocytes (Bourke et al, 1980;Gotoh et al, 1985;Iadecola, 1999;Kempski et al, 1991;Kimelberg, 1995Kimelberg, , 1999. Previous studies have shown that BBB breakdown, allowing paracellular flux of solute and water into the brain, generally occurs after 3 to 6 hours of continuous reduction in blood flow, and that the majority of edema formation is accounted for by the net uptake of brain cations and water that occurs well before BBB breakdown (Betz, 1996).…”
mentioning
confidence: 99%
“…This model is known to provide a reproducible and consistent lesion assessed by regional cerebral blood flow and the extent of the ischemic area. 13>25 We analyzed the time course of edema formation in the ischemic hemisphere of this model, 26 and we measured HETEs 24 hours after MCA occlusion, when the edema was progressing most rapidly, and at 72 hours, when the edema reached its maximum. In the brain rendered ischemic for 72 hours, the amounts of all 6 HETEs were increased, and the increases in 5-, 9-, 11-, and 15-HETE were significant.…”
mentioning
confidence: 99%